Reaction of rice varieties to rice leaf folder, Cnaphalocrocis medinalis Guenee in South Gujarat - Bairwa, KL; Ghoghari, PD; Jena, MK (ORYZA-An International Journal of Rice, 2023)
The rice leaf folder, Cnaphalocrocis medinalis (Guenee) is a serious pest causing a great reduction in the yield of rice during the vegetative stage. In this study, ten rice varieties NAUR-1, GNR-2, GNR-3, GNR-4, GNR-5, GNR-6, GNR-7, GR-15, GR-11, and TN-1, were screened to assess their reaction against C. medinalis at the Main Rice Research Centre Farm, Navsari Agricultural University, Navsari, Gujarat, India during Kharif-2021. The infestation of C. medinalis was recorded in all ten rice varieties at 30, 40, 50, 60, 70, 80, 90, 100 and 110 Days After Transplanting (DAT). The lowest infestation of C. medinalis was recorded in GR-15, GNR-7, GNR-3, GNR-6, GNR-5, GNR-2 and NAUR-1 (score 3) and higher infestation was recorded in GNR-4 (score 5). Whereas the highest infestation was recorded in GR-11 and TN-1 (score 7), in all the observation intervals which were stated as state and national susceptible check.